SUBSTANTIATION OF SELECTION FOR SCIENTIFIC AND METHODOLOGICAL SUPPORT OF DECISIONS FOR THE ORGANIZATION OF INTERACTION OF BORDER SECURITY SUBJECTS - Katerynchuk І. S.; Gulevatyi, D. Yu. (Honor and Law, 2019)
The possibilities of application of structural and functional analysis in the decision support system for the organization of interaction of border security subjects while performing tasks on the state border protection have been reviewed. The algorithm for solving the problem of the choice of rational variants for interaction of border security subjects has been improved.